PENERAPAN DATA MINING MENGGUNAKAN ASSOCIATION RULES UNTUK MENDUKUNG STRATEGI PEMASARAN - -, Nurjoko; Darmawan, Abdi (244-5567)
The rapid growth of data accumulation has created the conditions for data-rich but information poor. Data mining is the mining m or discovery of new information by looking for certain patterns or rules of a number of large amounts of data are expected to treat the condition. By utilizing the data of prospective students and student data, is expected to yield information about the resources used by the candidate that can be used by management in making efforts associated with an increase in the number of students by choosing the appropriate media campaign through data mining techniques.The algorithm used is the a priori algorithm, the information displayed in the form of support and confidence value of each pattern is formed. Of tests on the data of prospective students and student data with the model Association rules generated some rules with a maximum value of confidence level of 81.1% for resources from newspapers and media level maximum value of 77.8% confidence sebesarb to resources through the media brosur.Saatini right promotional media for use by TIMP emasaran in recruiting new students are media newspapers and brochures with not ignore other promotional media.Â Keywords: data mining, Association rules, a priori algorithm, confidence, support